Intellectual and Social Capital, Energy, and Resource Rents as Drivers of Economic Growth in Middle East and North Africa: Evidence from Panel ARDL Analysis - Fakhreddine, Nour; Taher, Hanadi; Mourad, Abbas (International Journal of Energy Economics and Policy, 2025)
This study examines the short- and long-term effects of intellectual capital (IC), social capital (SC), and natural resource rents, including energy rents, on economic growth in MENA countries. Using a panel ARDL model, the analysis covers knowledge-based assets, social networks, and dependence on natural and energy resources, while incorporating additional IC factors related to demographics, health, and poverty. The results show that IC has a strong positive effect on GDP, while SC alone has little impact. Resource and energy rents reduce growth, highlighting the risks of overreliance on extractive sectors. When IC and SC are combined, their effect on GDP becomes positive and significant, suggesting that social networks can enhance the effectiveness of knowledge-based assets. The study has practical value by pointing to policies that support innovation, skills development, and cooperation while reducing dependence on natural and energy rents. Theoretically, it extends endogenous growth and resource curse frameworks by showing how intangible and social capital jointly shape long-term economic performance in resource-dependent economies.